(untitled) (Bulletin of Pure and Applied Sciences – Physics, 2022)
Molecular dynamic study of benzene sulfonamide based compounds was carried out to compute several properties like phonon density of states, atomic electric potential and electric field gradient tensor components and then compared. This work establishes the correlation between physical properties and the quantity of carbon atoms in a molecule. The GULP program was used to do all the calculations and reported single crystal data.